The cultural construction of monstrous children : essays on anomalous children from 1595 to the present day - Bacon, Simon, 1965-; Ruickbie, Leo (London : Anthem Press, 2020)
This book raises important questions and presents important findings on socio-cultural representations and embodiments of the child and childhood. At the start of the twenty-first century, new anxieties constellate around the child and childhood, while older concerns have re-emerged, mutated, and grown stronger. But as historical analysis shows, they have been ever-present concerns. This innovative and interdisciplinary collection of essays considers examples of monstrous children since the sixteenth century to the present, spanning real-life and popular culture, to exhibit the manifestation of the Western cultural anxiety around the problematic, anomalous child as naughty, dangerous, or just plain evil. The linkage between children and horror, or horror-full children, would seem an almost natural connection to make given its popularity in contemporary horror films and novels. However, the intersection between the two categories has a long history going back beyond the more obvious Gothic reimaginings of the nineteenth century with its under-age ghostly terrors revealing that the idea of the 'little horror' is seemingly an inherent demarcation within society between adults and those that are viewed as 'not adults'. However, the anomalous child can also be seen in a positive light, and that resistance to easy categorization can be embraced by wider society as a force for change. Greta Thunberg, a singularly focused individual, 16 years old at the time of writing, has consistently refused to act as desired by the adult society around her in pursuit of gaining recognition of the urgent need for action in regard to environmental change. The book takes an inter- and multidisciplinary approach, drawing upon fields as diverse as sociology, psychology, film, and literature, to study the role of the child and childhood within contemporary Western culture and to see the ways in which each discipline intersects and influences the other, all through a historical lens.
Title from publisher's bibliographic system (viewed on 20 Jan 2022).
Keywords: Children -- History; Children in literature; Children in motion pictures; Monsters in popular culture; Good and evil